THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND DEPRESSION LEVEL AMONG HIV/AIDS PATIENTS IN PROF.DR. SOEKANDAR GENERAL HOSPITAL MOJOKERTO - Indra Yulianti; Veryudha Eka Prameswari; Tria Wahyuningrum; M.Haris Hadi Sururi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Problems that arise in people with HIV / AIDS not only from viral infections there are also social impacts experienced such as a lack of support from the family. The phenomenon that occurs in the community that shy families sometimes even ostracize people with HIV / AIDS so that when treatment is rarely delivered, isolating in the family such as placing in a separate room makes ODHA increasingly experiencing psychological disorders such as prolonged stress reactions, namely depression. The purpose of this study was to determine the relationship of family support with the level of depression in patients with HIV / AIDS in VCT poly RSUD Prof.Dr. Soekandar Mojokerto. The research design used is correlation analysis. The population in this study were all HIV / AIDS sufferers in the VCT Police Hospital, Prof. Dr. Soekandar, Mojokerto Regency, which consists of 51 patients. The Sampling technique uses consecutive sampling with a number of samples that meet the research criteria of 50 people. The instrument used is a questionnaire. After the data is collected, data processing is done in editing, coding, scoring, tabulation by using the frequency distribution and followed by cross tabulation (Crosstab). The results of the study were tested by the Spearman rho test. Obtained by the results of p (0,000) and α (0,05), so that p (0,000) <α (0,05) which means that H0 is rejected and H1 is accepted which means there is a relationship between family support and depression in HIV / AIDS patients in Poly VCT Rsud Prof. Dr. Soekandar Mojokerto. Family support is needed by patients with HIV / AIDS to reduce depression by providing support, providing facilitation, and assisting patients when at home or when going to the hospital.